Institutional theory and human resource management - Hashemi, Alireza (Routledge research in human resource management, 2026)
This research volume delves into the intricate realm of human resource management (HRM) through the lens of institutional theory.Spanning eight chapters, it meticulously explores the intersection of organizational studies and HRM, offering a deep understanding of how institutional contexts shape HRM practices and behaviors. Readers will gain a comprehensive understanding of the contextual approach in HRM and its linkage with institutional theory. By leveraging the insights provided, they can enhance their analytical skills, enrich their understanding of institutional complexities, and design effective HRM strategies tailored to organizational contexts. Key topics covered include institutional pressure, logic, action, response, work, and entrepreneurship in HRM, as well as micro-institutions and multi-level HRM approaches.This book will be of value to academics, researchers, and practitioners in the field of HRM seeking to deepen their understanding of the institutional underpinnings of HRM. It is also invaluable for advanced students studying HRM, organizational studies, or related disciplines, providing them with a solid theoretical foundation and practical insights for navigating the complexities of HRM in real-world contexts.